ANALISIS POTENSI DESTINASI WISATA HALAL DI DAERAH PESISIR SELATAN KABUPATEN BANGKALAN (KECAMATAN KAMAL, LABANG DAN KWANYAR) - Maya Apridia; Dahruji Dahruji (PROCEEDING UMSURABAYA, 2022)
ABSTRACT Madura Island consists of four Districts, namely Bangkalan Districts, Sampang Districts, Pamekasan Districts, and Sumenep Districts. Bangkalan District as the entrance to enter the island of Madura makes Bangkalan District, especially the southern coastal area, a very diverse potential for halal tourism destinations by utilizing the sea view and the Suramadu bridge, which can be seen from the coast. Halal tourism comes with a concept that provides services for vacations equipped with facilities for the needs of the Muslim community in carrying out worship activities. The research method used is qualitative with a descriptive approach. Data collection methods used in the form of observation, interviews, and documentation. The results of this study indicate that the southern coastal area of the Bangkalan Districts can apply the concept of halal tourism. Looking at some of the indicators that have been explained, which consist of Attractions, Accessibility, Amenities, and Additional Facilities that meet the criteria, but there are still some things that need to be improved with facilities and infrastructure and supported by regulations regarding Bangkalan District implementing the concept of halal tourism. Keywords                   : Bangkalan; Halal Tourism; Potential; Southern Coastal Area